Foundational films : early cinema and modernity in Brazil - Conde, Maite, 1971- (California scholarship online., 2018)
"In her authoritative new book, Maite Conde introduces readers to the crucial early years of Brazilian cinema. Focusing on silent film released during the First Republic (1889-1930), Foundational films explores how the medium became implicated in a larger project to transform Brazil into a modern nation. Analyzing an array of cinematic forms, from depictions of contemporary life, to fan magazines, to experimental avant-garde productions, Conde demonstrates the distinct ways in which Brazil's early film culture helped to project a new image of the country"--Provided by publisher.